Hydropriming Effect on Seed Germination Characteristics of Different Seed morphs of Golden columbine (Aquilegia chrysantha) - F. Nabi; A. Asgharzadeh; E. Ganji; A.R. Bagheri (علوم و فناوری بذر ایران)
Regarding importance of homogenous germination and to accelerate this stage of Aquilegia chrysantha a study was conducted with purpose of identification of different morph of seeds of A. chrysantha. Therefore, first the black and brown seeds were separated visually and then divided in two groups in term of size using machine vision method. The seeds were stored for four weeks at 4ₒC inrder to stimulate germination and after that the treatments of 4, 8, 12, 24 hours of hydropriming and control were applied on the seeds. The study was factorial and conducted in a completely randomized design. The factors include color and size of seeds and also hydropriming treatments. The results showed that large seeds in comparison with small seeds were better in traits including seed germination percentage, germination rate, and mean germination time. In addition black seeds have a better performance in mentioned traits than brown seeds. Also the best characteristics of germination were recorded in the 12 and 24 hours of hydropriming. Overall, using large black seeds in the 12 hours of hydropriming would have a good germination and is recommended for better production of A. chrysantha.